Study on the Effect of Irbesartan on Atrial Fibrillation Recurrence in Kumamoto: Atrial Fibrillation Suppression Trial (SILK study). Issue 2 (February 2018) - Yamabe, Hiroshige; Kaikita, Koichi; Matsumura, Toshiyuki; Iwasa, Atsushi; Koyama, Junjiro; Uemura, Takashi; Morikami, Yasuhiro; Tsunoda, Ryusuke; Morihisa, Kenji; Fujimoto, Kazuteru; Kajiwara, Ichiro; Matsui, Kunihiko; et al.
Highlights: Blood pressure decreased similarly in both the irbesartan and amlodipine groups. Changes in echocardiographic parameters and biomarkers were similar between two groups. No significant difference was found in atrial tachyarrhythmia recurrence between two groups. Interval from the procedure to recurrence was similar between two groups. Irbesartan had no advantage over amlodipine in the atrial tachyarrhythmia reduction. Abstract: Background: Experimental studies suggest that angiotensin II-receptor blockers can influence atrial remodeling and may prevent atrial fibrillation (AF). Therefore, we hypothesized that irbesartan may prevent the recurrence of AF following either catheter ablation or electrical cardioversion of AF. Methods: Study on the Effect of Irbesartan on Atrial Fibrillation Recurrence in Kumamoto (SILK study) is a prospective, multicenter, randomized, and open-label comparative evaluation of the effects of irbesartan and amlodipine on AF recurrence in hypertensive patients with AF who are scheduled to undergo catheter ablation or electrical cardioversion of AF. The primary end point was either AF or atrial tachycardia (AT) recurrence. AF/AT recurrence was evaluated for 6 months using 24-h Holter electrocardiogram and portable electrocardiogram. The secondary endpoints included the change in blood pressure, the interval from the procedure to the first AF/AT recurrence, cardiovascular events, left atrial diameter (LAD), left ventricular ejection fraction (LVEF), and changes in the biomarkers [brain natriuretic polypeptide (BNP), high-sensitivity C-reactive protein (hs-CRP), urinary albumin/creatinine]. Results: The study enrolled 98 patients (irbesartan; n = 47, amlodipine; n = 51). The recurrence of AF/AT was observed in 8 patients (17.0%) in the irbesartan group and in 10 patients (19.6%) in the amlodipine group. There was no significant difference in the AF/AT recurrence between the irbesartan and amlodipine groups. Blood pressure decreased similarly in both groups. There were no significant differences between the two groups as regards to the interval from the procedure to the first AF/AT recurrence, occurrence of cardiovascular events, changes in LAD and LVEF. BNP and urinary albumin/creatinine significantly decreased similarly in both groups, but no significant difference was found in hs-CRP between the two groups. Conclusions: In hypertensive patients with AF, treatment with irbesartan did not have any advantage over amlodipine in the reduction of AF/AT recurrence after catheter ablation or electrical cardioversion.